Understanding the relationship between perceived stress, academic motivation, and physical activity in college students during the coronavirus pandemic - Rahe, Martina; Jansen, Petra (Frontiers in Education, 2022)
The coronavirus pandemic has influenced the lives of many people. We analyzed the effects of physical activity and stress on students' motivation during the pandemic. Participants were 254 university students who reported their academic motivation, physical activity, general stress, the coronavirus pandemic strain, and their coronavirus stress. Women reported higher levels of coronavirus stress, general stress, and motivation. The coronavirus stress was predicted by the strain of the coronavirus pandemic but not by physical activity. General stress and gender predicted mastery goals, and performance goals were predicted by general stress. Physical activity was not related to students' motivation during the pandemic. Higher levels of general stress were associated with higher academic motivation. Negative emotions like stress could have enhanced students' motivation during uncertain times of the pandemic. Moreover, a moderate stress level could be favorable for academic dedication and achievement.